2008
DOI: 10.1080/13636820802042404
|View full text |Cite
|
Sign up to set email alerts
|

Preparing potential teachers for the transition from employment to teacher training: an evaluative case study of a Maths Enhancement Course

Abstract: In response to a UK government drive to improve maths teaching in schools, the South West London Maths Enhancement Course (MEC) has been set up though collaboration between three Higher Education institutions (HEIs) to provide an efficient route for non maths graduates in employment to upgrade their subject knowledge and give a smooth transition into teacher training (PGCE).An evaluation of the scheme, measured against Teacher Development Agency (TDA) objectives and success criteria agreed by university staff,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…Research showed the need to smooth the transition from student to employee (May et al 2008). Purdy and Gibson (2008) recommended the development of transferrable skills in teacher training through alternative placements to enhance employability at the point of qualification.…”
Section: Resultsmentioning
confidence: 99%
“…Research showed the need to smooth the transition from student to employee (May et al 2008). Purdy and Gibson (2008) recommended the development of transferrable skills in teacher training through alternative placements to enhance employability at the point of qualification.…”
Section: Resultsmentioning
confidence: 99%